Antibacterial activity of citrus sinesis peel extract against gram negative bacteria / Marini Wirasari - Wirasari, Marini (2018)
Sweet orange (Citrus sinensis) is a common fruit source of vitamins and fibers. It contains phytochemicals and phenolic compound that are proved to act as an antimicrobial agent However, a lot of waste produced by their peel has become a concern to the environment. Therefore, our prime aim was to evaluate the antibacterial activity of peel sweet orange against Gram negative bacteria as an alternative natural antibiotics. Methanol and aqueous extract were used to measure the antibacterial activity of sweet orange peel. Four different concentration (25, 50, 100 and 200) of both extract were evaluated against three different Gram negative bacteria which were Escherichia coli, Salmonella sp., and Shigella sp. Both extracts were prepared in a concentration of 25, 50, 100 and 200 mg/ml and findings showed that, both extracts does not exhibit any antibacterial activity against Gram negative bacteria tested. However, MIC of methanol extract was at 100 mg/ml while aqueous extract was above 100 mg/ml. Findings also showed that at lower concentration of 200 mg/ml, methanol and aqueous extract of peel sweet orange did not have any antibacterial activity against Escherichia coli, Salmonella sp., and Shigella sp. For further study, it could be improved by increasing the concentration of each extract and use other solvents extract such as ethanol and chloroform.